(untitled) (KONFERENSIYA, 2025)
This article discusses innovative methods of teaching foreign languages in modern education. It examines the role of digital technologies, interactive learning platforms, and student-centered approaches in improving language acquisition. The study highlights the effectiveness of communicative language teaching, blended learning, and project-based activities in enhancing learners’ linguistic competence and motivation. Practical recommendations are provided for integrating modern tools such as mobile applications, virtual classrooms, and gamification into the foreign language teaching process